1998
DOI: 10.1016/s0741-5214(98)70261-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function is a risk factor for paralysis in thoracoabdominal aortic replacement

Abstract: CSFD and low-dose naloxone significantly reduce the paralysis risk associated with thoracoabdominal aortic replacement. A decrease in the cardiac index with aortic occlusion is a previously unreported variable that defines a subset of patients at higher risk for paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 33 publications
5
50
0
1
Order By: Relevance
“…Even in such environments, operative mortality is generally in the 10% range, and spinal cord ischemic complications (SCI) remain in the 5% to 15% range. [1][2][3][4][5][6][7][8][9] Indeed, efforts to minimize the risk of SCI have been the principal impetus for the variety of operative strategies and protective adjuncts used during surgery. Clearly, there is no consensus on the major variants of operative approach (e.g., with or without some form of distal aortic perfusion) designed to minimize SCI, as reviewed elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Even in such environments, operative mortality is generally in the 10% range, and spinal cord ischemic complications (SCI) remain in the 5% to 15% range. [1][2][3][4][5][6][7][8][9] Indeed, efforts to minimize the risk of SCI have been the principal impetus for the variety of operative strategies and protective adjuncts used during surgery. Clearly, there is no consensus on the major variants of operative approach (e.g., with or without some form of distal aortic perfusion) designed to minimize SCI, as reviewed elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…35 Comparable results have been achieved in contemporary practice with the use of both clamp/sew and distal perfusion techniques. 4,5,28,36,37 In addition, atriofemoral bypass will provide easily titratable mechanical unloading of the left ventricle, and this may be desirable in patients with antecedent aortic valvular dysfunction or significant degrees of left ventricular dysfunction.…”
Section: Open Surgical Repairmentioning
confidence: 99%
“…6 Another negative predictor reported in the literature is advanced age, although we found that overall functional status is more important than chronological age per se. 4,32,56 The presence of increasing numbers of comorbid conditions can naturally be expected to increase overall operative risk. Individual series have demonstrated increased operative risks in patients with antecedent coronary artery disease, significant COPD, and, in particular, preoperative renal insufficiency.…”
Section: Conrad and Cambria Management Of Thoracoabdominal Aneurysms 843mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Patients at greatest risk are those with Crawford types I, II, or emergent dissection. 2,3 Factors postulated to decrease the incidence of paraplegia include decreased aortic cross-clamp time, reimplantation of intercostal arteries, hypothermia, or CSF drainage. 1 The proposed mechanism of the benefit of CSF drainage in paraparesis is reduction of CSF pressure and the improvement in spinal cord perfusion pressure.…”
Section: Reversal Of Paraparesis After Thoracic Aneurysm Repair By Cementioning
confidence: 99%